Lower levels of senescence in human lung mesenchymal stromal cells compared with lung fibroblasts: implications for tissue regeneration in COPD - Wisman, Marissa; Kruk, Dennis M. L. W.; Kooistra, Wierd; Heijink, Irene H.; Woldhuis, Roy R. (American journal of physiology. Lung cellular and molecular physiology, 2025)
We demonstrate that LMSCs are less sensitive to senescence induction by oxidative stress and replication than LFs, which was accompanied by an increased ability to expand. This makes LMSCs more suitable for cell-based therapies in COPD. As senescence affected growth factors involved in alveolar repair, specifically FGF10 expression in both LMSCs and LFs, we additionally suggest that the development of anti-senescence strategies may promote endogenous tissue repair in COPD. In patients with chronic obstructive pulmonary disease (COPD), lung-tissue regenerative mechanisms are thought to be exhausted, to which cellular senescence may contribute. Lung-derived mesenchymal stem/stromal cells (LMSCs) constitute a potent supportive cell type able to self-renew and promote alveolar regeneration. We hypothesized that LMSCs are less sensitive to senescence induction in COPD than other supportive cells, for example, lung fibroblasts (LFs), and therefore more promising in regenerative strategies. We compared senescence markers in LMSCs and LFs from the same subjects with/without replicative- and stress-induced senescence. LMSCs and LFs were isolated from COPD and non-COPD lung tissue using cell-specific protocols and expanded for multiple passages under the same culture conditions. Proliferation, senescence-associated β-galactosidase (SA-β-gal) activity, expression of senescence markers ( CDKN2A/P16, CDKN1A/P21, and LMNB1), P21 protein levels, secretion of senescence markers (IL-6 and IL-8), and alveolar growth factors [hepatocyte growth factor (HGF) and fibroblast growth factor 10 (FGF10)] were assessed in the absence/presence of paraquat (PQ). We observed higher population doublings, and lower SA-β-gal positive cells and P21 protein levels in LMSCs compared with LFs at baseline. COPD-derived LFs had lower population doublings and higher cellular size than controls, which was not observed for COPD-derived LMSCs. LMSCs displayed lower sensitivity to PQ-induced senescence compared with LFs (COPD and control combined). Senescence induction was accompanied by increased IL-6 and IL-8 secretion, to which fibroblasts were more sensitive, and by reduced FGF10 but not HGF expression in both cell types. This study demonstrates that LMSCs have lower levels of senescence and lower sensitivity toward senescence induction compared with LFs, affecting cell expansion and FGF10 expression. This suggests that LMSCs are better suited for cell-based therapies. NEW & NOTEWORTHY We demonstrate that LMSCs are less sensitive to senescence induction by oxidative stress and replication than LFs, which was accompanied by an increased ability to expand. This makes LMSCs more suitable for cell-based therapies in COPD. As senescence affected growth factors involved in alveolar repair, specifically FGF10 expression in both LMSCs and LFs, we additionally suggest that the development of anti-senescence strategies may promote endogenous tissue repair in COPD.